Necrotizing pancreatitis with portal vein thrombosis in young patient with COVID-19 - Abrar J. Alwaheed; Mohannad A. Alalwan; Hasan M. Aldakhlan; Feda H. Albeladi (Elsevier, 2022)
The current pandemic of the novel coronavirus disease 2019 (COVID-19) originated in Wuhan, China in December 2019. The most common clinical manifestations are fever, fatigue, and cough. Other common symptoms include anorexia, chest tightness and shortness of breath. Extrapulmonary manifestations including gastrointestinal symptoms were also reported in patients with COVID-19 infection. It has been found that the ACE2 receptor of SARS-CoV-2 is expressed more in the pancreas than in the lungs. However, only few cases reported with pancreatic injury were caused by COVID-19. In this paper, we report a young patient presenting with acute necrotizing pancreatitis that is complicated with portal vein thrombosis and found to have COVID-19 infection.